2015
DOI: 10.1096/fj.15-273607
|View full text |Cite
|
Sign up to set email alerts
|

Family with sequence similarity member 20C is the primary but not the only kinase for the small‐integrin‐binding ligand N‐linked glycoproteins in bone

Abstract: Recent studies have identified family with sequence similarity member 20C (FAM20C) as a kinase that phosphorylates the Ser in Ser-X-Glu/phospho-Ser (pSer) motifs in the small-integrin-binding ligand N-linked glycoproteins (SIBLINGs). There is no in vivo evidence that validates this finding, and it is unclear whether FAM20C is the only kinase for SIBLINGs. We extracted bone noncollagenous proteins (NCPs) from Fam20C-knockout (KO) mice and analyzed the phosphorylation levels. The total NCPs were separated into o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…These Sox2-Cre;Fam20C flox/flox mice also showed enamel and dentin defects 14 . The phosphorylation levels of non-collagenous proteins including DMP1 and OPN in the bone and dentin of Sox2-Cre ; Fam20C flox/flox mice were lower than in the normal mice 6 .…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…These Sox2-Cre;Fam20C flox/flox mice also showed enamel and dentin defects 14 . The phosphorylation levels of non-collagenous proteins including DMP1 and OPN in the bone and dentin of Sox2-Cre ; Fam20C flox/flox mice were lower than in the normal mice 6 .…”
Section: Introductionmentioning
confidence: 78%
“…DMP1 is a substrate of FAM20C 2, 6 . Without FAM20C, DMP1 cannot be properly phosphorylated, which may lead to the loss of its functions.…”
Section: Discussionmentioning
confidence: 99%
“…The five proteins do, however, share some structural similarities, such as the integrin-binding tripeptide Arg-Gly-Asp (RGD), several post-translational phosphorylation and N-glycosylation sites 8 . Traditionally, the SIBLING families are classified by exon-intron similarities and their biochemical properties in osteogenesis and biomineralization 9 . However, previous research suggested that SIBLING proteins expression is not only observed in mineralized tissues, but it is also observed in different tumor stages which are coupled with Matrix Metalloproteinases (MMPs).…”
Section: Structural Analysis Of Osteopontinmentioning
confidence: 99%
“…In FAM20C KO mice, OPN has been shown to be still phosphorylated at FAM20C recognition motifs. (31) This indicates that other kinases apart from FAM20C can phosphorylate the SIBLING proteins. In the present study, 22 phosphorylated residues were identified by LC-MS/MS in MEPE (not including the ASARM sequence) after coexpression with FAM20C, whereas only a single phosphoserine residue was identified when MEPE was expressed alone.…”
Section: Discussionmentioning
confidence: 99%